Tinea incognito due to microsporum gypseum - Yu, Chunshui (Editorial Department of Journal of Biomedical Research, 2010)
A 41-year-old woman presented with a pruritic rash on the face that was of 3 months duration. During that time, it had been successively misdiagnosed as psoriasis vulgaris, systemic lupus erythematosus, facial dermatitis at other hospitals, and had been treated with agents that included acitretin and prednisone. Finally, fungi were found in the lesions by optical microscopy, and the fungal culture was positive for Microsporum gypseum, and was diagnosed as a Microsporum gypseum infection. The lesions eventually cleared completely after 8 weeks of antifungal treatment.